Synthesis, antimalarial activity evaluation and molecular docking studies of some novel dispiro-1,2,4,5-tetraoxanes (Bangladesh Journal of Pharmacology, 2015)
Seven novel dispiro-1,2,4,5-tetraoxane derivatives were synthesized and characterized by a number of analytical and spectroscopic techniques. The molecules were subsequently screened for in vitro antimalarial activity against chloroquine resistant strain of Plasmodium falciparum (RKL-9). At antimalarial activity screening, two compounds, namely 5d (MIC = 15.6 µg/mL or 64.5 µM) and 5f (MIC = 15.6 µg/mL or 54.6 µM) were found to be about 1.5 times more potent against chloroquine resistant strain-RKL-9 compared to chloroquine (MIC = 25.0 µg/mL or 78.3 µM). Molecular docking studies of potent ligands were also performed in cysteine protease binding pocket residues of falcipain-2 as a target protein.